An Empirical test of a Judgemental International Classification of Financial Reporting Practices - Doupnik, Timothy S.; Salter, Stephen B. (Journal of International Business Studies, 1993)
The main objectives of this study were to (1) empirically classify current national financial reporting systems and (2) test the validity of a hierarchical classification proposed by Nobes [1983] and extended by Berry [1987]. Data on accounting practices were obtained for fifty countries and used as input into a hierarchical cluster analysis. The resulting classification bears significant similarity to the aforementioned taxonomies and provides several additional insights.